Macro-historical influences, cohort dynamics, and the (in)stability of the age–crime distribution: the case of the Republic of Korea - Kang, Byunggu (Criminology, 2024)
Crime is often considered a behavior of teenagers and young adults, peaking in adolescence, and declining with age. A growing body of research, however, has demonstrated that the age-crime relationship is neither universal, as the contours of the age-crime distribution vary across countries, nor uniform, as it varies over time. We argue that the dynamics of the age-crime relationship can best be understood through a lens situating birth cohorts within the broader sociohistorical contexts in which they enter their formative years. We apply this framework to the Republic of Korea, a country that has experienced rapid demographic transitions accompanied by decades of economic development and social upheaval after the Korean War. Our findings suggest that the age-crime distribution in Korea has shifted substantially since the mid-1970s, moving from the quintessential age-crime curve characteristic of Western countries to one in which the modal age at arrest is now concentrated in middle age. We find that much of this change can be attributed to the aging of a specific birth cohort—the 86 generation—whose members were dually disadvantaged by being born during a fertility boom and entering young adulthood during the pro-democracy student movements in the 1980s.